2006
DOI: 10.1007/s11524-005-9012-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Moisture or Mildew in the Homes of Head Start Children with Asthma is Associated with Greater Asthma Morbidity

Abstract: This study used results from a cross-sectional survey of parents of 3- to 5-year-old children with asthma to assess the frequency of self-reported home environmental conditions that could contribute to worsening asthma and examined the relationship between these factors and the child's asthma morbidity. Participants were 149 parents drawn from the two largest agencies that provide subsidized preschool childcare services in East and Central Harlem, inner-city communities with high prevalence of asthma. The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 12 publications
2
18
0
1
Order By: Relevance
“…9 This finding is consistent with many studies of inner city housing which have demonstrated higher levels of asthma triggers, including molds, than housing in general. [21][22][23][24][25][26] In conclusion, analysis of the 36 molds that make up the ERMI provided a more objective way to describe the mold burdens in homes. However, we recognize that each mold inspector has his/her own methods, years of experience, and equipment for finding mold growth.…”
Section: Discussionmentioning
confidence: 98%
“…9 This finding is consistent with many studies of inner city housing which have demonstrated higher levels of asthma triggers, including molds, than housing in general. [21][22][23][24][25][26] In conclusion, analysis of the 36 molds that make up the ERMI provided a more objective way to describe the mold burdens in homes. However, we recognize that each mold inspector has his/her own methods, years of experience, and equipment for finding mold growth.…”
Section: Discussionmentioning
confidence: 98%
“…1 Greater asthma morbidity, specifically a larger number of hospitalizations due to asthma, more frequent episodes of wheezing, and more frequent night symptoms due to asthma have been associated with the presence of moisture, mildew, and cockroach allergen in homes. 22,23 The presence of these allergens may be more common in deteriorating housing, which is often marked by water leaks, holes that pests can pass through, poor ventilation, and peeling paint.…”
Section: Introductionmentioning
confidence: 99%
“…Conditions that may indicate underlying housing disrepair, such as mold (which was strongly but not significantly associated with detectable allergen and rodent sighting), have previously been associated with increased allergen and with greater asthma morbidity 18,20 as well as with pest infestation. Having unwashed dishes, and having crumbs on the floors because of lack of a working vacuum cleaner may provide access to food and water that could attract rodents, but which are potentially amenable to intervention at modest cost.…”
mentioning
confidence: 96%